2001
DOI: 10.1111/j.0014-3820.2001.tb01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetic Markers to Directly Estimate Male Selection Gradients

Abstract: Abstract. We present an analysis of Raphanus raphanistrum and simulations illustrating the utility of directly estimating male phenotypic selection gradients using genetic markers. The method offers a much more refined characterization of selection than attempting to assign paternity to individual progeny. Our analysis of R. raphanistrum reveals selection on remarkably fine features of floral morphology, including anther exsertion, that were opaque to previous approaches. The new results also undermine a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 56 publications
4
125
0
Order By: Relevance
“…Most wild radish floral correlations are low to moderate (0.28 -0.59), with the exception of the three correlations among the short and long filaments (the filaments mainly determine the length of the stamens) and the corolla tube ( [22]; table 2). We have evidence for stabilizing selection through lifetime male seed siring success on the difference in lengths between the long filament and corolla tube (anther exsertion; [24]) and on the difference in lengths between the two filaments [25]. Stabilizing selection on the difference between two traits is evidence for correlational selection to increase the correlation between the two traits [26,27].…”
Section: Discussionmentioning
confidence: 91%
“…Most wild radish floral correlations are low to moderate (0.28 -0.59), with the exception of the three correlations among the short and long filaments (the filaments mainly determine the length of the stamens) and the corolla tube ( [22]; table 2). We have evidence for stabilizing selection through lifetime male seed siring success on the difference in lengths between the long filament and corolla tube (anther exsertion; [24]) and on the difference in lengths between the two filaments [25]. Stabilizing selection on the difference between two traits is evidence for correlational selection to increase the correlation between the two traits [26,27].…”
Section: Discussionmentioning
confidence: 91%
“…The current analyses based on paternal probability models and maximum likelihood methods revealed many more significant paternal selection gradients in addition, indicating that the low number of significant paternal selection gradients found by van Kleunen and Ritland (2004) are mainly a consequence of the low power of the analyses. Similarly, in a reanalysis of data on floral traits of Raphanus raphanistrum that had previously been analysed with standard regression methods by Conner et al (1996), Morgan and Conner (2001) also found more significant paternal selection gradients when they used the maximum-likelihood approach. This supports our result indicating that the maximum-likelihood approach is much more powerful than simple regression of male fertility estimates on traits of interest.…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…Because estimates of paternity are more accurate when all potential males in a population are sampled, other studies on paternal selection were restricted to artificial (Morgan and Conner 2001;Elle and Meagher 2000;Conner et al 2003) or relatively small (<500 flowering plants) natural (Smouse et al 1999;Vassiliadis et al 2002;Wright and Meagher 2004) populations. A simulation study by Morgan and Conner (2001) showed that sampling only a fraction of the potential males in a population reduces the power to detect significant selection and underestimates the magnitude of the selection gradients.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations